Noninvasive measurement of pressure gradient across a coronary stenosis using phase contrast (PC)‐MRI: A feasibility study. Issue 2 (26th December 2016) - Deng, Zixin; Fan, Zhaoyang; Lee, Sang‐Eun; Nguyen, Christopher; Xie, Yibin; Pang, Jianing; Bi, Xiaoming; Yang, Qi; Choi, Byoung‐Wook; Kim, Jung‐Sun; Berman, Daniel; Chang, Hyuk‐Jae; et al.
Abstract : Purpose: To investigate the feasibility of blood pressure difference measurement, ΔP, across the coronary artery using phase contrast (PC)‐MRI for potential noninvasive assessment of the functional significance of coronary artery stenosis. Methods: Three‐directional velocities in the coronary arteries acquired using 2D‐PC‐MRI were used with the Navier‐Stokes equations to derive ΔP. Repeat phantom studies were performed to assess the reproducibility of flow velocity and ΔP. ΔP derived using PC‐MRI (ΔPMR ) and that obtained using pressure transducer (ΔPPT ) were compared. Reproducibility of coronary flow velocity was assessed in healthy controls (n = 11). Patients with suspected coronary artery disease (n = 6) were studied to evaluate the feasibility of ΔPMR measurement across a coronary stenosis. Results: Phantom : Good overall reproducibility of flow velocity and ΔP measurements and excellent correlation (ΔPMR vs ΔPPT ) was observed: intraclass correlation (ICC) of 0.95(Vz ), 0.72(Vx ), 0.73(Vy ), and 0.87(ΔPMR ) and R 2  = 0.94, respectively. Human : Good reproducibility of coronary flow velocity was observed: ICC of 0.94/0.95(Vz ), 0.76/0.74(Vx ), and 0.80/0.77(Vy ) at cardiac phase 1/2. Significant ( p  = 0.025) increase in ΔPMR was observed in patients (6.40 ± 4.43 mmHg) versus controls (0.70 ± 0.57 mmHg). Conclusion: ΔPMR in the coronary arteries is feasible. Upon further validation using the invasive measure, ΔPMR has the potential for noninvasive assessment of coronary artery stenosis. Magn Reson Med 77:529–537, 2017. © 2016 International Society for Magnetic Resonance in Medicine.